ANALISIS PENGELOLAAN PIUTANG USAHA PADA HOTEL SERAYU (JURNAL ULET (Utility, Earning and Tax), 2024)
This research aims to determine the billing turnover rate, average billing collection days, and billing performance based on billing activities carried out by Hotel Serayu Timika. This research is descriptive research with data collection techniques using observation, interviews and documentation techniques. The data analysis instruments used in this research are analysis of the billing turnover rate, average billing collection days, arrears ratio and collection ratio. The results of the analysis show that the overall billing turnover rate at the Serayu Hotel can be said to be very effective, even though there was a decline in 2020, this can be proven by a significant increase in 2021. The average billing collection days can be said to be very efficient in collection activities. Hotel Serayu seen from the arrears ratio and collection ratio, it can be concluded that the collection activities at Hotel Serayu are not good enough.